Exploring impacts of process technology development and regional factors on life cycle greenhouse gas emissions of corn stover ethanol - McKechnie, Jon; Pourbafrani, Mohammad; Saville, Bradley A.; MacLean, Heather L. (Elsevier, 2015)
This paper examines impacts of regional factors affecting biomass and process input supply chains and ongoing technology development on the life cycle greenhouse gas (GHG) emissions of ethanol production from corn stover in the U.S. Corn stover supply results in GHG emissions from -6 gCO2eq./MJ ethanol (Macon County, Missouri) to 13 gCO2eq./MJ ethanol (Hardin County, Iowa), reflecting location-specific soil carbon and N2O emissions responses to stover removal. Biorefinery emissions based on the 2011 National Renewable Energy Laboratory (NREL) process model are the single greatest emissions source (18 gCO2eq./MJ ethanol) and are approximately double those assessed for the 2002 NREL design model, due primarily to the inclusion of GHG-intensive inputs (caustic, ammonia, glucose). Energy demands of on-site enzyme production included in the 2011 design contribute to reducing the electricity co-product and associated emissions credit, which is also dependent on the GHG-intensity of regional electricity supply. Life cycle emissions vary between 1.5 and 22 gCO2eq./MJ ethanol (2011 design) depending on production location (98% to 77% reduction vs. gasoline). Using system expansion for co-product allocation, ethanol production in studied locations meet the Energy Independence and Security Act emissions requirements for cellulosic biofuels; however, regional factors and on-going technology developments significantly influence these results.